Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1007/s11517-020-02272-z
|View full text |Cite
|
Sign up to set email alerts
|

Approaches for determining cardiac bidomain conductivity values: progress and challenges

Abstract: Modelling the electrical activity of the heart is an important tool for understanding electrical function in various diseases and conduction disorders. Clearly, for model results to be useful, it is necessary to have accurate inputs for the models, in particular the commonly used bidomain model. However, there are only three sets of experimentally determined four conductivity values for cardiac ventricular tissue and these are inconsistent, were measured around forty years ago, often produce different results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 102 publications
(232 reference statements)
1
25
0
Order By: Relevance
“…In these settings, in fact, we observed that the asymmetry of the reference CV isoline in parametric space translates into different dynamical scenarios depending on the particular choice of the (σ i , σ e ) pair, with larger values of the conductivity parameter corresponding to the highest fractional exponent typically giving richer dynamics in terms of alternans and node formation. This adds to the challenges already existing for the classical Bidomain formulation in the proper estimation of suitable conductivities [59] and undoubtedly requires further investigation in higher spatial dimensions to better elucidate the effects of non-locality in either (or both) spatial domains. Finally, in line with well-established results for the standard case, for any particular parameter combination of the FBD we observe richer dynamical responses (allowing the formation of discordant alternans -if previously absent -and potentially increasing the number of nodes formed at a given BCL) when increasing the cable length or reducing the reference CV.…”
Section: Discussionmentioning
confidence: 99%
“…In these settings, in fact, we observed that the asymmetry of the reference CV isoline in parametric space translates into different dynamical scenarios depending on the particular choice of the (σ i , σ e ) pair, with larger values of the conductivity parameter corresponding to the highest fractional exponent typically giving richer dynamics in terms of alternans and node formation. This adds to the challenges already existing for the classical Bidomain formulation in the proper estimation of suitable conductivities [59] and undoubtedly requires further investigation in higher spatial dimensions to better elucidate the effects of non-locality in either (or both) spatial domains. Finally, in line with well-established results for the standard case, for any particular parameter combination of the FBD we observe richer dynamical responses (allowing the formation of discordant alternans -if previously absent -and potentially increasing the number of nodes formed at a given BCL) when increasing the cable length or reducing the reference CV.…”
Section: Discussionmentioning
confidence: 99%
“…A lack of understanding of cardiac tissue's electrical properties is one of the major challenges in being able to realistically simulate cardiac electrophysiological behaviour [1,2,3]. Such simulations can facilitate an understanding that often cannot be achieved through experimental means alone.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in the past decade have proposed various techniques for retrieving all six bidomain conductivities, through either experimental and theoretical means [13,14], while several other studies were able to experimentally retrieve a subset of the conductivities [15,16,17]. However, no study has fully retrieved these values through purely experimental means [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to fibrosis and changes in interstitial space, the clefts that separate myocyte sheets modulates the conductivity of ES. The anisotropy of the ES conductivity is well-established and less pronounced than the anisotropy of the myocyte domain (Johnston and Johnston, 2020). Hence the bidomain model is more appropriate to describe features of fibrotic remodeling in cardiac tissues.…”
Section: Introductionmentioning
confidence: 99%